Sistem Deteksi Bahasa Isyarat Alfabet Menggunakan Dataset American Sign Language (ASL) dan Algoritma Random Forest - Siti Farah Fakhirah; Muhammad Fillah Alfatih; Hasna Nabiilah Widiani; Thoriq Muhammad Pasya; Endang Purnama Giri; Gema Parasti Mindara (Jurnal Sistem Informasi dan Ilmu Komputer, 2024)
Introducing alphabetical sign language is necessary to bridge communication between deaf and hard-of-hearing people and their surrounding environment. This research aims to develop a sign language alphabet letter detection system based on American Sign Language (ASL). The research methods include data collection, feature extraction with OpenCV and Mediapipe, model development with Random Forest algorithm, and real-time system testing. The test results show that the developed system can achieve 97% prediction accuracy in recognizing hand patterns that represent ASL letters. The system uses a webcam as real-time input, providing accurate responses in various environmental conditions. This research contributes significantly to developing communication support technology for the deaf community, with implications for increased inclusivity and social engagement.